2016
DOI: 10.17219/dmp/63185
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Immediate Maxillary Dental Implant Placement and Bone Resorption: A Review of the Literature and an Outlook on the Clinical Possibilities

Abstract: The insertion of dental implants immediately after teeth extractions has become a routine clinical procedure in implant dentistry, despite difficulties derived from several factors influencing bone resorption. The aim of this study is to evaluate the survival rate of implant positioned immediately after tooth extraction in the upper maxilla and to analyze the surgical techniques and the parameters to minimize physiological bone resorption. An electronic search in MEDLINE (PubMed) and the Cochrane library was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…1 Any microorganism is capable of causing bacteremia, especially in patients with serious underlying diseases or immunocompromised patients. However, the present literature supports the conclusion that the incidence of Lactobacillus bacteraemia is inconsistent and that all cases where individuals were recorded had other systemic diseases such as diabetes, cardiovascular disease, gastrointestinal disease, malignant tumors, or transplanted organs [19]- [28].…”
Section: Discussionsupporting
confidence: 76%
“…1 Any microorganism is capable of causing bacteremia, especially in patients with serious underlying diseases or immunocompromised patients. However, the present literature supports the conclusion that the incidence of Lactobacillus bacteraemia is inconsistent and that all cases where individuals were recorded had other systemic diseases such as diabetes, cardiovascular disease, gastrointestinal disease, malignant tumors, or transplanted organs [19]- [28].…”
Section: Discussionsupporting
confidence: 76%
“…There are conflicting opinions on the correlation between age and root resorption. It was found that in younger patients, the anatomical environment was more favorable because the presence of cementoid and predentine localized on the tooth apex constituted a protective factor [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%